Pengembangan Alat Portabel Pengukur Kadar Air dan Suhu Biji Kopi Berbasis ESP32 dengan Sensor Kapasitif dan Penyimpanan Data Real-Time - Ardianto Syaifur Rohman; Mochamad Irwan Nari; Daniel Fernando Siahan; Mursit Jamil; Atalarick Dwi Novial Kurniawan; Sihmaulana Dwianto; Tunjung Genarsih; Sepdian Luri Asmono (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
The primary quality indicator of coffee beans is determined by their moisture content. This study aims to develop a portable prototype device for measuring both the moisture content and temperature of coffee beans, utilizing an ESP32 microcontroller integrated with a Capacitive Soil Moisture Sensor v1.0 and an SHT21 sensor. The device is designed to provide accurate and efficient measurements, with results displayed in real time on an OLED screen. In addition, the system stores measurement data on an SD card for further analysis. Experimental testing was conducted five times for each sample, comparing the results of the prototype with reference instruments, namely the YL-69 sensor for moisture measurement and a digital thermometer for temperature measurement. The results demonstrated that the device achieved a high level of accuracy, with an average relative error of 1.05% for moisture content and 0.91% for temperature. Furthermore, the prototype was proven to be portable and energy-efficient, consuming 7.7 Wh over 1.1 hours of operation, as evaluated through battery-based performance testing until full discharge. With its integrated data storage and real-time monitoring capabilities, this device provides a practical solution for coffee farmers and processors in maintaining and ensuring the quality of coffee beans.